Development and Characterization of a Photopolymeric Binder for Additively Manufactured Composite Solid Propellant Using Vibration Assisted Printing. Issue 6 (23rd March 2020) - McClain, Monique S.; Afriat, Aaron; Rhoads, Jeffrey F.; Gunduz, Ibrahim Emre; Son, Steven F.
Abstract: An emerging area of research in the energetic materials community is the development of new manufacturing methods, such as additive manufacturing (AM), that can be used to selectively deposit energetic materials into complex geometries, which provides more control over how the energetics perform during combustion. Although ammonium perchlorate (AP) composite propellant has been 3D printed at solids loadings that are comparable to traditional formulations (85 wt.%) with vibration assisted printing (VAP), traditional propellant binders such as hydroxyl terminated polybutadiene (HTPB) are poorly suited for 3D printing large or complex structures because propellant made with HTPB deforms easily under its own weight and isocyanates do not crosslink HTPB fast enough to facilitate rapid polymerization after deposition. Ultraviolet (UV) curable photopolymers have been used for many types of AM processes, such as stereolithography, and there is a variety of commercially available binders with customizable chemical and mechanical properties. However, little work has been done to characterize the optimal cure characteristics of UV curable binders that are compatible with composite propellants. Furthermore, it has also been speculated that aluminized propellants may not be amenable to UV curing since opaque particles impede UV transmission. In this work, the curing properties of a photopolymer that has similar characteristics to HTPB with AP and aluminum were quantified. The ingredients consisted of a polybutadiene urethane acrylate and hexanediol diacrylate (HDDA) polymer binder, which could be mixed in various ratios to control properties such as adhesion to particle surfaces and viscosity, as well as bisacylphosphine oxide (BAPO) which is a well‐known photoinitiator for deep curing in the coatings industry. The effect of wavelength, exposure time, and intensity on cure depth were quantified on the neat photopolymer. In addition, the effect of aluminum content (up to 20 %) on the cure depth of propellant with a solids loading of 85 wt.% was measured. It was shown that at higher intensities (∼20 mW/cm 2 ), aluminized propellants could be cured to depths on the order of 1–2 mm, which is greater than the typical layer thickness of propellants printed via VAP (∼0.25 mm). In addition, it was shown that there were no visible interfaces in aluminized propellant (15 % aluminum) that was cured layer‐by‐layer. The approach taken could be applied to a wide range of other granular, opaque composite materials, such as metal, ceramic, and fibrous mixtures. Abstract :